2013
DOI: 10.1093/brain/awt073
|View full text |Cite
|
Sign up to set email alerts
|

Migrating partial seizures of infancy: expansion of the electroclinical, radiological and pathological disease spectrum

Abstract: Migrating partial seizures of infancy, also known as epilepsy of infancy with migrating focal seizures, is a rare early infantile epileptic encephalopathy with poor prognosis, presenting with focal seizures in the first year of life. A national surveillance study was undertaken in conjunction with the British Paediatric Neurology Surveillance Unit to further define the clinical, pathological and molecular genetic features of this disorder. Fourteen children with migrating partial seizures of infancy were repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
166
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 144 publications
(178 citation statements)
references
References 34 publications
11
166
1
Order By: Relevance
“…25,26 Phenotypic features that distinguish SCN2A-associated EIMFS from KCNT1-associated EIMFS 25 include severe movement disorders and response to phenytoin in some patients. Two patients showed a considerably better outcome than is usual for EIMFS.…”
Section: -Ax T-ap E-hv/t/ht I Gi-c Sf T2-wm T1-bg T-s T-ests Usmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Phenotypic features that distinguish SCN2A-associated EIMFS from KCNT1-associated EIMFS 25 include severe movement disorders and response to phenytoin in some patients. Two patients showed a considerably better outcome than is usual for EIMFS.…”
Section: -Ax T-ap E-hv/t/ht I Gi-c Sf T2-wm T1-bg T-s T-ests Usmentioning
confidence: 99%
“…While Dravet syndrome is differentiated by age at onset and seizure types, rare cases of EIMFS due to SCN1A mutations are described. 26,36,38 SCN8A encephalopathy can present with early-onset EE and responds to sodium channel blockers 27,30,39 in contradistinction to SCN1A diseases. 38,40 However, the median age at onset of 5 months for SCN8A is later, [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,27 which may reflect the respective patterns of expression of the subunits.…”
Section: -Ax T-ap E-hv/t/ht I Gi-c Sf T2-wm T1-bg T-s T-ests Usmentioning
confidence: 99%
“…In the last decade research has also shown that these channels have additional modulatory functions, which are regulated by a number of signaling pathways [5][6] . The majority of the recently identified mutations [7][8][9][10] are situated in the c-terminus of the alpha subunit of KCNT1, where modulatory regions, such as the NAD + binding domain [5] and several putative consensus sites for protein kinase C (PKC) [6] are located. Emerging evidence indicates that subtle changes in the function of this channel have a deleterious impact on the fragile developing brain [7][8][9][10] .…”
Section: Research Highlightmentioning
confidence: 99%
“…The majority of the recently identified mutations [7][8][9][10] are situated in the c-terminus of the alpha subunit of KCNT1, where modulatory regions, such as the NAD + binding domain [5] and several putative consensus sites for protein kinase C (PKC) [6] are located. Emerging evidence indicates that subtle changes in the function of this channel have a deleterious impact on the fragile developing brain [7][8][9][10] . Our latest study sought to examine the functional phenotype of KCNT1 mutations associated with these early-onset epileptic syndromes.…”
Section: Research Highlightmentioning
confidence: 99%
See 1 more Smart Citation